Marketplace Sebagai Sarana Pemasaran Jasa Kreatif: Studi Kasus Pada UMKM - Robby Williams; Riki Riki (ALGOR, 2026)
Advances in information technology have driven major transformations in business, particularly through e-commerce and marketplaces that facilitate online transactions. One of the advantages is that buyers can order goods or services online without having to visit the store in person. However, data from the Central Statistics Agency shows that many businesses are still not involved in e-commerce, and the adoption of marketplaces is still lagging behind the use of instant messaging and social media. Based on this phenomenon, this study designed a web-based marketplace platform specifically for service products that can accommodate various business processes from different services. This application is expected to accommodate conventional service businesses by providing marketing facilities, expanding the reach of buyers, and facilitating the search for services. The system design uses the prototype method through the stages of needs analysis, prototype design, evaluation, coding, testing, and implementation. The results of the study show that the designed platform can accommodate various service business processes.